Desain Mata Kuliah Edupreneur Pendidikan Islam dalam Mengembangkan Kemampuan Kreatif dan Inovatif bagi Mahasiswa Program Studi Pendidikan Agama Islam di Institut Agama Islam Nahdlatul Ulama Tuban - Fendi Prasetyo Utomo; Muslimin Muslimin (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study aims to analyze the design of the Islamic Education Edupreneurship course in developing the creative and innovative abilities of students in the Islamic Education Program (PAI) at IAINU Tuban. The study emphasizes the importance of strengthening entrepreneurial competencies among students to address employment challenges and reduce educated unemployment. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving lecturers and students. The findings reveal that the course design was developed through several components, including learning outcomes oriented toward entrepreneurial competence, integration of Islamic educational values with entrepreneurship materials, project-based learning strategies, and practice-based evaluation systems. The implementation of project-based learning encouraged students to develop creativity in designing educational products and strengthened innovation through real business practices in Islamic education. In addition, the course contributed to the formation of independent, adaptive, and solution-oriented entrepreneurial character among students. Therefore, the Islamic Education Edupreneurship course plays an important role in improving the quality and competitiveness of PAI graduates.